Character Development: Contributions from Undergraduate Activities and Interactions - Michael D. Thompson (Journal of Educational Issues, 2024)
This examination assessed the significant contributions of institutional activities and interactions regarding students’ character development within a liberal arts institutional setting. Data elements from four classes of alumni participants were utilized and extracted from the Higher Education Data Sharing Consortium’s Alumni Surveys. The results of this exercise confirmed many established outcomes concerning student character development, in addition to substantiating assertions concerning which college relationships and experiences have the greatest impact in contributing to its enhancement.